Design and Technical Evaluation of a Tempeh Slicer Using Stainless Steel Rotating Disc with Three Curved Blades - Tasliman Tasliman; Ahmad Mutafakkir Alam; Adetrio Santoso; Yoga Dwi Bahrul Habib; Dedy Wirawan Soedibyo (The University of Lampung, 2025)
A tempeh chips slicing machine has been developed. This machine was developed based from the results of the previous research. The main slicing component is a stainless steel rotating disc equipped with three curved knives. With this knives geometry arrangement, slicing can be done at high speed. High speed is possible due to the absence of reciprocating motion and due to smooth cutting strokes. A variable speed 550W brush less direct current motor was employed to power the slicing mechanism. The machine was tested at motor speed of 500, 600, 700, 800 and 900 rpm. Across all speeds, the machine consistently produced chips of 1 mm thickness that is in compliance with industrial requirement. The machine produced up to 96% of intact slices, with slicing capacity of 53 kg/h (692 slices/min) and a very low electric power consumption ranged from 23 W (at 500 rpm) to 60 W (at 900 rpm). The machine can slice several chip solid materials with good results, therefore it has the potential to be developed into a multi purpose chip slicer. Keywords: Curved rotary knife, Low power consumption, Slicer, Slicing machine, Tapioca tempeh chip.